2019
DOI: 10.26737/jetl.v4i2.803
|View full text |Cite
|
Sign up to set email alerts
|

the Effect of Problem-Posing and Think-Pair-Share Learning Models on Students’ Mathematical Problem-Solving Skills and Mathematical Communication Skills

Abstract: The main purpose of this study was to compare and examine the effectiveness of problem-posing and think-pair-share cooperatives' learning models on mathematical problem-solving skills and mathematical communication skills. This study was experimental research with a quasi-experimental design. The samples of the study were 41 students for classroom experiments and 40 students for classroom control. The instruments employed in this study were pre-test and post-test. The instruments were made in essay forms which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
3
0
3
Order By: Relevance
“…It has been shown that the results of the teaching process, which included learning activities based on the ACODESA method and mind mapping, have improved students' mathematical communication abilities. This study produced results that corroborate the findings of a great deal of the previous work in mathematics education (Hitt and Gonz alez-Martín, 2015;Setiyani et al, 2020;Yaniawati et al, 2019;Rohim and Umam, 2019). After a period of experimental teaching, the shortcomings mentioned above are gradually overcome.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It has been shown that the results of the teaching process, which included learning activities based on the ACODESA method and mind mapping, have improved students' mathematical communication abilities. This study produced results that corroborate the findings of a great deal of the previous work in mathematics education (Hitt and Gonz alez-Martín, 2015;Setiyani et al, 2020;Yaniawati et al, 2019;Rohim and Umam, 2019). After a period of experimental teaching, the shortcomings mentioned above are gradually overcome.…”
Section: Discussionsupporting
confidence: 88%
“…Aside from that, the authors have pointed out differences in the effects of problem-based learning (Hidayati et al, 2020;Sudia and Muhammad, 2020); and another study is based on project-based learning models without scaffolding (Paruntu et al, 2018). Meanwhile, some authors hope to improve students' mathematical communication skills through learning models such as digital teaching module (Setiyani et al, 2020), cooperative learning (Salsabil et al, 2017), ASSURE learning (Sundayana et al, 2017), learning devices based on constructivism approach (Zulaika and Syarifuddin, 2018), problem-posing and think-pair-share learning models (Rohim and Umam, 2019), school location (Juliarta and Landong, 2020), self-regulated learning (Sudia and Muhammad, 2020), quantum learning (Utari et al, 2020). Reikerås (2020) says that in toddlers, play abilities and mathematical abilities are linked, including the capability for mathematical communication.…”
Section: The Ways Of Developing Students' Mathematical Communication Skills In Some Specific Topicsmentioning
confidence: 99%
“…This is relevant to the TPS model that also provides opportunities for students to analyse their answers and also to share their answers with other students who are their partners. This learning model encourages students to improve problem management skills through conveying ideas and opinions to friends (Rohim & Umam, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Setelah dibandingkan ternyata penerapan strategi TPS di SD Negeri 3 ngadirojo lebih baik daripada penerapan strategi Jigsaw di SD Negeri 4 ngadirojo. Hasil penelitian ini sesuai dengan (Umam, 2019) menjelaskan bahwa TPS efektif dalam kemampuan pemecahan masalah. Jika dibandingkan dengan Jigsaw, maka jigsaw lebih banyak memerlukan persiapan dan dan koordinasi kelas yang baik agar dapat mengarahkan keterlibatan siswa secara maksimal (Liao, Griswold, dan Porter 2018).…”
Section: Printed Issn 2406-8012unclassified